Constructing a social accounting matrix with a distributional focus: the case of Bolivia - Rainer Thiele; Daniel Piazolo (Kiel Institute of World Economics (IfW), 2002)
This paper describes the construction of a Social Accounting Matrix (SAM) for Bolivia for the year 1997. Three distinctive features render the SAM a useful starting point for distributional analyses. First, production in the agricultural and services sector is split up into formal and informal activities to account for the fact that poverty is largely confined to the latter. Second, factor and household accounts exhibit a high level of disaggregation, thus permitting the monitoring of the factorial and personal income distribution. Finally, the SAM contains a detailed system of accumulation balances which reveals the distribution of assets among household groups.
Keywords: O54; D57; 330; structural adjustment programs; poverty; income distribution; Bolivia; SAM; Social Accounting Matrix; Funktionelle Einkommensverteilung; Einkommensverteilung; Vermögensverteilung; Armut; Bolivien